Aerospace series. Bolts, normal hexagonal head, coarse tolerance shank, short thread, in heat resisting nickel base alloy, aluminium IVD coated. Classification: 1 250 MPa (at ambient temperature) / 425 °C. (31st March 2016) - British Standards Institution,
No abstract available